Control of parasitoid invaders limiting production of the flour moth - da Costa Júnior, Domicio Pereira [UNESP]; Peixoto, Marília Lara; Zampieron, Sônia Lúcia Modesto; Putti, Fernando Ferrari [UNESP] (My University, 2017)
Current research evaluates a novel methodology in the production of the flour moth (Anagasta Kuehniella) by isolating the parasitoid Bracon hebetor and comparing production between the already employed production method (conventional) and the proposed one (experimental). Paper isolated the parasitoid Bracon hebetor from the production of Anagasta Kuehniella, with full efficiency from the attacks of the parasitoid Bracon hebetor, whereas the lots from the conventional treatment were attacked by the parasitoids. There was no significant difference in the production of adults and Anagasta Kuehniella eggs in all treatments. The two methods were efficient with regard to production and productivity. The proposed method is highly recommended due to its efficient isolation from the attacks of the parasitoid Bracon hebetor.
Keywords: Anagasta kuehniella; Bracon hebetor; Ectoparasitoid